2015
DOI: 10.5296/ajfa.v7i1.7598
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Market Value and Accounting Numbers of Firms in Pakistan

Abstract: This study examines the relationship between accounting numbers and market prices for the Pakistani cement industry. The study covers a time span of nine years from 2005-2014. We study the influence of book value of share, breakup value of share, earning per share, gearing ratio and dividend to equity ratio on market value of share. After applying different econometric techniques we found that book value of share and earnings per share have statistically significant influence on the market price of share.Keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…But a negative relationship between net asset value per share and stock price change was found by a study in Dhaka Stock Exchange consisting of 105 companies from 2000 to 2010 by Miah (2012). Most recently in a study in Pakistan by Riaz, Liu, and Khan (2015) ; Omura (2005) found that book value of share and earnings per share have statistically significant influence on the market price of stock So, it is found that although book value per share and stock price movement is positively linked in various developed and developing countries but in Dhaka Stock Exchange book value per share and stock price are negatively linked that represents a irrational behavior by the retail investor and finally resulted in market crash in 2011. Even after this big crash, Dhaka Stock Exchange represented stock prices volatility during last few years.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…But a negative relationship between net asset value per share and stock price change was found by a study in Dhaka Stock Exchange consisting of 105 companies from 2000 to 2010 by Miah (2012). Most recently in a study in Pakistan by Riaz, Liu, and Khan (2015) ; Omura (2005) found that book value of share and earnings per share have statistically significant influence on the market price of stock So, it is found that although book value per share and stock price movement is positively linked in various developed and developing countries but in Dhaka Stock Exchange book value per share and stock price are negatively linked that represents a irrational behavior by the retail investor and finally resulted in market crash in 2011. Even after this big crash, Dhaka Stock Exchange represented stock prices volatility during last few years.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Halonen, Pavlovia, and Pearson (2013) conducted a research in Swedish stock market and found that accounting information such as EPS and NAVPS are able to clarify a significant part of stock price. Riaz, Liu, and Khan (2015) also reported a statistically significant influence of EPS and BVPS on the MVPS. Omokhudu and Ibadin (2015) studied the VARI in Nigeria from 1994 to 2013 and concluded that in Nigeria accounting information like earnings, dividends, and cash flows are statistically significant and has the value relevance.…”
Section: Literature Reviewmentioning
confidence: 87%